Results of Water Inflow Elimination in Wells Draining Gas Сondestate Deposits - E. Vaganov; S. Sokhoshko; A. Sarancha; E. Levitina; I. Krasnov; T. Kharitonova (Наука. Инновации. Технологии)
Introduction. The difficult geological, physical and technological conditions for the development of gas condensate fields in the Far North lead to the fact that they are prematurely flooded with formation waters. One of the factors influencing the process of flooding «Valanginian» wells is the quality of cementing. It was revealed that the main watering of wells occurs due to a violation of the tightness of the annulus. Based on the results of work to eliminate water inflows in the wells of the Beregovoy and Urengoy fields, a two- and three-composite technology was tested, which proved an increase in the success of VIR.Materials and methods of research. The field practice of carrying out measures to eliminate water inflows (WLI) in wells has shown the effectiveness of the technology according to a two-three-component scheme. At the initial stage of LPW implementation, a water-repellent agent is used, which has selective filterability in the most permeable and watered reservoir intervals. Then, a water-blocking composition with high thermal stability based on alkali metal silicates (liquid glass) or compositions based on polyacrylamide, etc. is pumped. The requirements for reliable isolation of formation water breakthrough are imposed on compositions with different physical and chemical properties. At the final stage, the first two compositions are fixed with a composition with high adhesion to the rock (cement-based with various composition additives) to reinforce the waterproofing screen.Results and Discussion. To eliminate water inflows in wells, despite the difference in the geological structure between the Urengoy and Beregovoye fields, the compositions used have fluidity (low viscosity) while maintaining its stability in the process of performing a full cycle of activities. The work experience has shown the prospects of the technology aimed at the success of LSP in the «Valanginian» wells. The gelation period is adjustable and the formulations are resistant to formation water dilution. The results of previous well workovers in 2015 by the Urengoy UIRS showed a low success rate of about 30%. The low efficiency is associated with insufficient injection pressure at the final stage of the insulating composition into the reservoir, etc. The implementation of LSP in the «Valanginian» wells according to the implemented technology using a multicomponent additive based on biopolymers has shown effectiveness. At the same time, the natural permeability of the reservoir is preserved. So in 2016, the success of VIR increased and amounted to 70%. The effect was obtained from the implementation of the same technology of VIR at well No. 252 of the Beregovoye field with the use of a complex additive.Conclusion. Thus, based on the results of the liquidation of water inflows in wells draining the Valanginian gas condensate deposits of the Beregovoy and Urengoy fields, the improved two- and three-composite technology proved to be successful. Also, promising insulating compositions aimed at the effectiveness of LPV have been identified. The use of technology with a multi-component additive based on biopolymers has proven its effectiveness. Thus, in 2016, the success of VIR at the «Valanginian» wells of the Urengoyskoye field increased and amounted to 70%. This technology was used to perform a design and survey work at well No.252 of the Beregovoe field. As a result of the elimination of behind-thecasing flows from the underlying aquifer, a positive effect was obtained. This well is currently working in a gas gathering reservoir.